Medical mineralogy and geochemistry - Sahai, Nita; Schoonen, Martin A. A., 1960- (Reviews in mineralogy and geochemistry ;, 2006)
Reviews in Mineralogy & Geochemistry (RiMG) volumes contain concise advances in theoretical and/or applied mineralogy, crystallography, petrology, and geochemistry.